EKSISTENSI DINAS PEMBERDAYAAN PEREMPUAN DAN ANAK TERHADAP PELECEHAN SEKSUAL DI KABUPATEN BULUKUMBA PERSPEKTIF SIYASAH SYAR'IYYAH - Anton, Nurfadillah; Tenripadang, Andi; Larissa, Dea (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
The purpose of this study was to determine the form of service at the Bulukumba Religious Court Office, a study of Siyasah Syar'iyyah and the public's views regarding the quality of public services at the Bulukumba Religious Court Office. The method used in this research is a qualitative field (field research) with a normative theological approach and a fiqh siyasa approach, the data are primary and secondary data obtained through observation, interviews and literature. The results of this study indicate: 1) The forms of services for the Bulukumba Religious Court are court administration services, legal aid services and complaints and requests for information. 2) The public's perception of the performance of the Women and Children Empowerment Service is in accordance with the results of interviews with the public's perception of the performance of the Women and Children Empowerment Office in Kab. Bulukumba has 2 different versions, starting from the performance of the Women and Children Empowerment Service which has not been maximized due to the lack of campaigns/socialization related to empowering women and children so that many local people do not know what the duties and functions of the Women and Children Empowerment Service are and there are also those who think that it is already done. carry out their duties and functions in accordance with Standard Operating Procedures (SOP) well because many repressive efforts have been made to empower women and protect children.